CERTAIN ASPECTS OF TRADEMARK RIGHTS PROTECTION FOR GOODS AND SERVICES - Netska, Lyubov; Havva, Sofia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to identify, on the basis of judicial practice, relevant categories of disputes related to the protection of rights to signs for goods and services. Formulation of recommendations aimed at improving the judicial protection of trademark rights. Research methods: formal-legal, system-functional, analysis and synthesis, modeling. Results: the main criterion characteristics of a trademark, important for the protection of intellectual property rights to it, are outlined. It has been established that judicial protection of trademark rights for goods and services is the most expedient and effective. It has been found that for a positive resolution of litigation in cases of protection of trademark rights, it is necessary to correctly choose and justify the methods of protection, to provide the court with sufficient and convincing evidence of infringement of intellectual property rights, to apply the conclusions and approaches to the resolution of trademark cases formed by the Supreme Court. Discussion: problems that arise in the protection of rights to signs for goods and services; methods of protecting intellectual property rights to signs for goods and services, defined by law or contract; opportunities to protect rights to a well-known trademark; competition of trademark and industrial design rights and its impact on the protection of intellectual property rights. An important component of the effective protection of trademark rights is a proper understanding by the owners of their rights and the possibilities they have in the event of an infringement committed against them. Of key importance is the correct choice of adequate methods of protecting trademark rights, their justification, submission to the court of appropriate, admissible, reliable and credible evidence: compliance of the trademark with the criteria of legal protection, independent use of this object of intellectual property, violation of the rights to the trademark by another person (individuals), consumer perceptions of the trademark and its perception, etc.